2021
DOI: 10.3390/ijerph18136769
|View full text |Cite
|
Sign up to set email alerts
|

Male Barroom Aggression among Members of the Australian Construction Industry: Associations with Heavy Episodic Drinking, Trait Variables and Masculinity Factors

Abstract: Introduction and Aims: Past research indicates heavy episodic drinking (HED), trait aggression, male honour and conformity to masculine norms are risk factors for male barroom aggression (MBA) perpetration. However, little is known about the impact of these variables on experiences of MBA victimization. Further, data derived previously, particularly in relation to perpetration have come from relatively low-risk samples comprising university students, limiting the generalizability of findings to other, at-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Additionally, wall-object punching has been linked to both anger and impulsivity, such that the association between impulsivity and wall-object punching is indirectly related via anger (Patel et al, 2022). The Emotional Control masculine norm has similarly shown strong associations with impulsivity (Litherland et al, 2021) and anger (Salgado et al, 2019). As such, future research should seek to further examine the role of the Emotional Control norm in these pathways to determine if adherence to this masculine gender role norm may play a casual role in the engagement of wall-object punching in Veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, wall-object punching has been linked to both anger and impulsivity, such that the association between impulsivity and wall-object punching is indirectly related via anger (Patel et al, 2022). The Emotional Control masculine norm has similarly shown strong associations with impulsivity (Litherland et al, 2021) and anger (Salgado et al, 2019). As such, future research should seek to further examine the role of the Emotional Control norm in these pathways to determine if adherence to this masculine gender role norm may play a casual role in the engagement of wall-object punching in Veterans.…”
Section: Discussionmentioning
confidence: 99%
“…They may be increasingly excluded from healthier social groups and gravitate towards others with more chaotic and even antisocial behaviour, placing them in situations where victimisation is more likely. Research has indicated that both heavy‐episodic drinking and greater association with deviant peers are risk factors for victimisation (Litherland et al., 2021; Testa et al., 2019; Vézina et al., 2011; Wojciechowski, 2022). Because alcohol‐related disorders are positively associated with both (Coder et al., 2009; Jenkins et al., 2011; Miranda et al., 2013; Sloan et al., 2011), there is a potential that either or both mediate the relationship between alcohol dependence and victimisation.…”
Section: Introductionmentioning
confidence: 99%